Hematological Studies during Endotoxin Infusion in Rabbits - Graeff, H; Beller, F. K (Thrombosis and Haemostasis, 1968)
Endotoxin was infused over 14 hrs into rabbits at a rate of 30-50 μg/kg/hr. During the infusion of endotoxin the following parameters were observed:a) The leukocytes declined in the early phase of the experiment but increased after 2 hrs despite continuation of the infusion.b) Hemolysis in a range of 130-180 mg% plasma hemoglobin was present in animals at the time glomerular fibrin deposition was observed.c) Platelets declined steadily until the end of the infusion.d) Factor V declined during the infusion and reached levels below 10% of baseline (normal) levels.e) The thrombelastogram revealed an increase in the r value and a decrease in mε.f) Fibrinogeng) plasminogen andh) streptokinase inhibitor decreased initially reaching a plateau after 6 hrs.i) Plasmin inhibitor andj) urokinase inhibitor did not change during the period of observation.k) Fibrin split products were demonstrated in 4 out of 7 serum samples taken 14 hrs following the initiation of the infusion.I) C’activity decreased during infusion of endotoxin.